ʻAllāmah Ṣalāḥ al-Dīn Saljūqī - Saljūqī, Ḥusayn Vafā (Silsilah-i Nasharāt-i Ittiḥādīyah-i Zhūrnalistān, 1987)
On the life and works of Ṣalāḥ al-Dīn Saljūqī, a writer, journalist and philosopher of Afghanistan.